Is being a 'left-behind' child associated with an increased risk of self-poisoning in adulthood? Findings from a case–control study in Sri Lanka - David Gunnell; Paul Moran; Laura D Howe; Duleeka Knipe; Piumee Bandara; Thilini Rajapakse; Kolitha Wickramage (BMJ Global Health)
Purpose The long-term consequences of parental emigration on offspring self-harm risk is unknown.Methods We investigated the association between experiencing parental emigration in childhood with hospital presentations for self-poisoning in adulthood using a hospital case–control study. Cases were adult self-poisoning patients (≥18 year olds) admitted to the medical toxicology ward Teaching Hospital Peradeniya, Sri Lanka. Sex and age frequency matched controls were recruited from the outpatient department or nearby specialist clinics at the same hospital. Details of parental emigration were collected using a pre-piloted questionnaire. The relationship between parental emigration and self-poisoning in adulthood was estimated using logistic regression models.Results 298 cases, and 500 hospital controls were interviewed for the study. We estimate that one in five adults experienced parental emmigration as children (95% CI 17% to 24%). We find limited evidence that children from households with emigrating parents were more likely to experience adverse childhood experiences than those with non-emigrating parents. We found no statistical evidence of an increased risk of self-poisoning in adulthood in individuals who experienced parental emigration (maternal or paternal) during childhood. There was no statistical evidence that the impact differed by the sex of the participant.Conclusion Adults who experienced parental emigration as children were no more likely to self-poison than adults with non-emigrating parents. Further research using longitudinal data are needed to understand whether any adverse outcomes observed in 'left-behind' children are a consequence of parental emigration or due to factors associated but predate the emigration. Prospective data are also important to investigate whether there are any lasting effects on children who experience parental emigration.